Contrast agents for ultrasound examination - S. V. Fomina; V. D. Zavadovskaya; M. S. Yusubov; L. A. Drygunova; V. D. Filimonov (Бюллетень сибирской медицины)
Ultrasound examination is the integral component of diagnostic imaging and it is widely used method for medical visualization in Russian clinical medicine. Modern diagnostic imaging inseparably linked with use of contrast agents. Currently, the use of echo-contrast agents is a compulsory condition for patient's examination with constant improvement and development of new echo-contrast agents. In Russia these agents are not widely used due to insufficient duration contrast procedure and high cost of examination. However, during the last years there are factors promoting the development and introduction of echo-contrast agents into the national market.